SISTEM INFORMASI PENERIMAAN SISWA/I BARU BERBASIS WEB PADA SMP NEGERI 01 SEMENDAWAI TIMUR MENGGUNAKAN PHP DAN MYSQL: - - hartati, sri (SISKOMTI: Jurnal Sistem Informasi Komputer dan Teknologi Informasi, 2021)
Admission of new learners (PPDB) Online is a system designed to conduct automatic selection ranging from registration, selection process to selection announcement process. This online PPDB system is expected to be able to meet the expectations of SMP Negeri 01 Semendawai Timur about the implementation of acceptance of new learners who are objective, transparent and accountable.In this study, the author used interview methods, reference methods and observation methods in the creation of online registration websites. It uses a variety of software, programming languages, and frameworks such as Sublime Text, PhpMyAdmin Codeigniter, CSS and HTML.This research contains such as registration flow, PPDB information, registration requirements, school contacts, student biodata, student biodata print and announcement print, re-listing schedule, admin can verify participants, edit and delete participants' data and approve participants.